Genetics of Ankylosing Spondylitis—Focusing on the Ethnic Difference Between East Asia and Europe - Wu, Xin; Wang, Geng; Zhang, Luding; Xu, Huji (Frontiers in Genetics, 2021)
Ankylosing Spondylitis (AS) is a common, highly heritable inflammatory arthritis affecting the mainly axial joints in both East Asia and Europe. To date, the pathogenesis of AS is still unknown, although we know that genetics play a vital role in it. The HLA-B27 allele is found in over 85% AS patients. However, strong evidence suggests that other major histocompatibility complex (MHC) and non-MHC genes are also involved in the pathogenesis. In addition, current data showed there were significant differences in both genomics and metagenomics among the different ethnic populations. The investigation of the key role of the microbiome in AS pathogenesis also highlighted the host-microbiome genetic interactions. Here we systematically review current AS genetic research data, and further compare genetic differences, especially between East Asian and European groups, which may highlight the challenge in future genetic studies.